60 A joint effort against COVID-19: leading a remote regional training programme and collaborating with the british society for rheumatology (BSR) on a national level. (16th November 2020) - Man, Yik Long; Ludwig, Dalia; Glanville, James; Pollard, Louise C; Gorman, Claire; Mukherjee, Jaita; Logan, Victoria; Coakley, Gerald; Galloway, James
Abstract : COVID-19 has had a significant impact on specialty training. All training days were cancelled and the majority of trainees were redeployed to general medicine. By early May 2020, there was a shift in the focus back towards specialty training as COVID-19 related hospital admissions continued to decrease. With the help of the team from King's College London, a remote rheumatology training programme was developed and accessible to trainees from four different regions – South London, North West London, North East/North Central London and Kent/Surrey/Sussex. The collaboration between different regions gave access to a greater pool of speakers and reduced the administrative workload. Subsequent collaboration with the British Society for Rheumatology facilitated the delivery of the webinars on a national level, supporting other regions that had not yet set up any remote training. Feedback was particularly important for this innovative programme in order to understand how this experience could be optimised for trainees. There were no additional difficulties related to the training taking place online, with one trainee responding that it was 'very easy to log on'. There was also positive feedback regarding the recording – '[it] was great to have a link to the recording to watch it later'. By having a shared vision for change, we were able to work across regions and organisations, delivering a high quality training programme on a national scale, benefitting a greater number of trainees. Remote training has the additional benefit of removing the need to travel between hospitals. Therefore, there may be a push towards blended learning (a combination of online and face-to-face learning) in the future. Using a robust feedback mechanism, we are confident that the programme will continue to improve as it evolves alongside the pandemic, aiming to at least in part, satisfy the speciality rheumatology training needs within our regions.